Is processing speed predictive of functional outcome in psychosis? - Jabben, N; van Os, J; Burns, T; Creed, F; Tattan, T; Green, J; Tyrer, P; Murray, R; Krabbendam, L (2008)
OBJECTIVE: To investigate the contribution of processing speed in the prediction of various domains of outcome in psychosis. METHOD: Data were drawn from the UK700 Case Management Trial of 708 patients with chronic psychotic illness. Regression analyses were applied to investigate cross-sectional and longitudinal associations between processing speed at baseline and measures of service use, social outcome and subjective outcome, taking into account current psychopathology and adjusting for baseline values of the outcome measure. RESULTS: Cross-sectionally, processing speed was associated with all three domains of outcome, although only associations in the social and subjective outcome domain remained significant after controlling for psychopathology and the effects differed between and within domains of outcome. Prospectively, only the subjective outcome measure of number of met and unmet needs (CAN) was weakly associated with baseline neurocognitive performance after adjustment for baseline needs. Other associations disappeared after adjustment for the baseline measure of outcome and/or baseline psychopathology. CONCLUSION: The finding of weak cross-sectional associations in the absence of specific and unconfounded longitudinal associations suggests that processing speed is an independent dimension of disease severity rather than a causal factor impacting on social outcome. Nevertheless, longitudinal change in patient reported needs may be weakly sensitive to baseline cognitive impairment.